THE CORRELATION OF EDUCATION AND SOCIAL ECONOMIC LEVELS WITH ANTIBIOTIC SELF-MEDICATION IN THE COMMUNITY OF CIREBON - Tridaya Putri Handayani; Muhammad Duddy Satrianugraha; Witri Pratiwi; Ruri Eka Maryam Mulyaningsih (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: People in developing countries, like Indonesia, often conduct self-medication. One of the most common drugs used in self-medication is antibiotics. Antibiotics should be used with caution since it can cause antibiotic resistance and possible unwanted side effects of the drug. There are several factors that influence self-medication behavior such as education and socio-economic levels. This research aims to find the correlation between education and social economic levels with antibiotic self-medication in the community of Cirebon.Method: This study was an analytical survey with cross-sectional method. This study was conducted from December 2018 to February 2019. A total of 300 respondents were recruited as samples using consecutive sampling technique. The respondents were recruited from 5 different pharmacies from each sub-district in Cirebon City and a validated questionnaire were used to obtain data. The collected data are analyzed using the Spearman correlation test.Results: The results of this study show that there was a significant but weak positive correlation of education level (r=0.224, p=0.001) and socio-economic (r=0.210, p=0.001) with self-medication using antibiotics. Conclusion: There is a significant positive correlation between education and socio-economic levels with antibiotic self-medication.